Performance-Measurement Analysis Of 3G GSM For Managing The Congestion In WCDMA (3GPP) - Kaur, Gurmeet (My University, 2008)
This project is aimed at analysis of 3rd generation GSM network performance statics for managing the congestion in radio resources and towards addressing the problem related with performance. Resource management is a crucial aspect in the next generation cellular network since use of WCDMA technology give inherent flexibility managing the system capacity. Universal Mobile Telecommunication Systems (UMTS) is third generation cellular technology representing the evolution of a heterogeneous mix of services and increased the data speeds from the today second’s generation mobile networks. UMTS uses Wideband Code Division Multiple Code Access (WCDMA) as a radio interface. The implementation of WCDMA is technical challenge because of complexity and versatility. To exploit the flexibility of air interface of, development of Radio Resources Management scheme are imperative, RRM is the compromise of power control, handover control, load control and resource allocation algorithm. These insure the maximum network coverage, and guarantee Quality of Services (Qos) requirement. In this project 3rd generation GSM network performance and performance analysis are discussed to managing the congestion. As simulation result, simulation tools are developed that can be used when the radio network performance investigated, the effect of various parameter on performance discussed. The main scheme consider here are; site planning, adding more E’1 for increasing the system capacity, carrier addition and expansion ,adaptive multi rate(AMR) codec, half rate configuration. A particular the novel aspect of this work is use of learning to predict the control strategies to be imposed for managing the congestion, as, a system environment changes, and the most suitable policy will be implemented. When congestion occur the system either proposes the solution by recalling from experience (if the event is similar to what has been previously solved) or recalculates the from its solution (if event is new) . With this system approach, the system performance will be monitored at all times and suitable policy can be immediately applied as system environment changes, resulting in maintaining the system quality of services.
M.E.
Keywords: CDMA